Self-Directed Language Learning with Duolingo - Lisma Martarini; Agus Iswara (Indonesian Journal Publisher, 2025)
The ability to speak foreign languages, especially English, is becoming increasingly important in this era. Mastering a foreign language not only opens up wider career opportunities but also allows individuals to interact with different cultures and societies. Along with the development of technology, methods of foreign language learning have also undergone transformation. One increasingly popular approach is self-directed language learning (SDL). Currently, there are various language learning applications available, one of which is Duolingo. Duolingo is a popular and widely used language learning application around the world. This application offers a variety of interesting features, such as gamification, interactive exercises, and instant feedback. There are several stages involved in this research: (1) preparation, (2) implementation, and (3) evaluation. Data collection was carried out thru literature studies and observation of the research object. In this study, the researcher used a qualitative approach.